(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Anorexia is an eating and psychological disorder that is characterized by restricted nutrient consumption relative to requirements, leading to malnutrition and underweight. Patients have severe fear of gaining body weight, they eat less, exercise more or purge foods by using laxatives, diuretics or through vomiting. They even may have distorted body image with the incapability to recognize the seriousness of their extremely low body weight. Anorexia is more common among females than males. Risk factors include family history, mental and emotional stress, childhood obesity, mood disorders, sexual abuse, family or peer pressure, history of dieting, personality traits etc. Treatment includes weight gain, psychological therapy for stress management and treatment of complications.